The Statement of Erhasat (Unusual Events Simultaneous with the Birth of Prophet Mohammad (PBUH) in the Writings from the 2nd to the 7th century (A. H) - Mehdi Olyaee Torqabeh; Mahmood Mahdavi Damghani; Shahrbanoo Dlbary (تاریخ اسلام)
The historians and biographers were of different approaches in dealing with the statement of Erhasat (unusual events simultaneous with the birth of Prophet Mohammad (PBUH)). A group of authors have mentioned only one case of Erhasat, while some others have mentioned all of them, and some have contributed these issues to the time of Prophet’s mission. This article is to investigate the news of Erhasat and the reasons for its writing or non-writing in the Islamic and Iranian historical writings until the 7th century (A. H). The findings of this research indicate that the historians with the religious bias as well as the authors of the books of Dalael al-Nabowah have stated Erhasat, while the historians with the rationalist thoughts have refrained from its statement.